Tools for assessing quality of life in epilepsy patients. (December 2013) - Jacoby, Ann; Baker, Gus A; Crossley, Joanne; Schachter, Steven
In this review, we attempt to bring the reader up to date with recent developments in the area of assessment of quality of life (QOL) of patients with epilepsy, in both the research and clinical contexts. We present evidence from recent publications on the major and most commonly used QOL instruments for both adults and children with epilepsy, including both strengths and limitations. We discuss both generic measures and ones that have been developed specifically for use in the epilepsy population. We draw attention to some of the broader issues that render the QOL assessment endeavor a somewhat complex one – in particular, that epilepsy is not a single condition, with a common clinical trajectory; and that QOL measures as currently configured almost universally focus on its negative impacts, largely neglecting the possibility of those affected being able to retain reasonable social adjustment and life satisfaction. Finally, we suggest that further work needs to focus on plugging the current evidence gaps in relation to psychometric and cross-cultural applicability issues; and on the value of QOL instruments in the clinical care setting. We conclude by highlighting a number of issues from the QOL literature that will, in our view, be the focus of increasing research interest in the next few years.